The supportive care needs for prostate cancer patients in Sarawak - Cheah, W.L; Ling, Ngok Chuo; Chang, Kam Hock (Society for Translational Medicine (STM), Hong Kon, 2016)
Background: This cross-sectional study aimed to determine the prevalence of unmet supportive care needs among prostate cancer patients. Methods: The cross-sectional study was conducted among all prostate cancer patients at the Sarawak General Hospital. Interview was done using the Supportive Care Needs Survey-Short Form (SCNS-SF) and the Health Service Utilization Questionnaires (HSUQ). Data were analysed using Statistical Package for the Social Sciences (SPSS) 20. Results: A total of ninety-five patients participated, with majority were aged 65 and above and of primary educational level. The two most frequently reported unmet supportive care needs were “informed about cancer which is under control or diminishing” and “informed about things you can do to help yourself to get well” under the domain Health System and Information. Respondents who were older (65 years and above) had significant lower unmet needs in psychology (P<0.01), and sexuality compared to the younger group below 65 years (P<0.01). Except for physical and daily living, respondents with primary school level had significant lower unmet needs in all domains compared to secondary school level. Respondents with known stages of cancer had higher unmet needs in all domains compared to those who did not know. Conclusions: Healthcare providers should provide more responsive, emotionally sensitive and client centered care to patients with prostate cancer, particularly in the area of Health System and Information, and psychological support.